A comparative study of multidimensional talent in field hockey at development stage between the players of Germany and Pakistan - Ashgar, E. (2012)
The main purpose of this comparative study between German and Pakistani Field Hockey players at the talent development stage (12-18 years) was to reveal multidimensional performance characteristics, which may have power for predicting future talented elite Field Hockey players. In total 271 (German 127 & 144 Pakistani) participants took part in this comparative study to find out difference in psychological, physical and social profiles and their possible influences on the performance of the players on two occasions, each separated by a time interval of one year. The mean age for German players was 14.3 years and Pakistani players 16.3 years. Data were collected from players of various institutions and clubs of both countries. Later on, researcher included Bangladesh, India and Sri Lanka in the study to increase the number of participants considering that South Asian culture is similar and Field Hockey is a popular game in the region. This addition will give strength to the study to find out the real differences in the performance of South Asian and European countries. In total, (227) 41 Indian, 40 Bengali and 44 Sri Lankan, 52 Pakistani and 50 German athletes took part in the study. The mean age for Indian was 14.5 years, Sri Lankan 15.3 years, Bangladeshi 15.7 years, Pakistani 16.9 years and German athletes were 15.5 years old. The Deutsch and English language standard sport questionnaires were used to measure the variables and data were analysed with the help of SPSS - 17 version. The following variables were put to test to find out the possible difference between the young players: Goal orientation in sports, General sport ability & appearance, Perceived physical self-concept, Competition related anxiety, Coping strategies, Sport commitment, Parental support, Coaches behaviour, Motivational climate and Selfefficacy in sports. The study shows that there were significant differences in psychological, physical and social profiles in the players of both countries. German players reported higher scores in motivation, perceived physical self-concept, self-confidence and commitment to the sport and found better to overcome anxiety and situation related problems. They were more social, and had full support from families, peers and coaches who can increase motivational climate to improve performance level, but contrary to expectations, Pakistani players reported a higher incidence of coping strategies. Reasons for the results are discussed with regard to differences i